Rancang Bangun Sistem Informasi Desa “BERSINAR” (Bersih Narkoba) Berbasis Website Menggunakan Metode Rapid Application Development (RAD): Studi Kasus Bnn Kabupaten Trenggalek - Fahrezi, Dion Maulana; Cahyono, Taufiq Agung; Prasetya, Agung (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to design and develop a website-based *Desa Bersinar* Information System and to evaluate its functionality and usability. The research employed the Rapid Application Development (RAD) methodology, comprising requirements planning, user design, construction, and cutover phases. Data were gathered through observation, interviews, and literature reviews. The system was developed using the Laravel framework and a MySQL database. Functionality was tested using Black Box Testing, while usability was assessed via a Likert-scale questionnaire administered to 10 respondents. Test results indicated that all tested features—including login, reporting, village data, articles, and the gallery—functioned according to the established scenarios. Usability testing yielded a score of 341 out of a maximum of 500 (68.2%), placing it in the "good" category. These results demonstrate that the system is user-friendly and capable of supporting the dissemination of P4GN (Drug Abuse Prevention, Eradication, and Handling) information, as well as the centralized management of data, documentation, and community reports. Consequently, the developed information system can serve as a tool to support the digitalization of *Desa Bersinar* Program management at BNN Trenggalek Regency